PERANCANGAN ANIMASI CERITA WAYANG SEBAGAI MEDIA PEMBELAJARAN PADA SISWA KELAS V SD NEGERI KUTOSARI 02 GRINGSING - Ary Setiaji (STEKOM PRESS, 2017)
This study aims to design learning media that can increase enthusiasm, motivation, and understanding of students, and can facilitate teachers in learning Javanese subjects with material listening to the Werkudara puppet story. The method used in research is R&D (Research and Development) while the method used in the development of instructional media is the waterfall method. The story developed is a story with the title (1) Butcher Bilawa, (2) Bima Bungkus, and (3) Bima Suci. To produce a learning media researchers use a design processing program including; Adobe Photoshop CC, Adobe After Effects CS6, Adobe Audition CS6, Pinnacle Studio 16, Adobe Flash CS6 with the final product in the form of an interactive CD. The results of the assessment by media experts and material experts, get the criteria value